Experimental demonstration of dyed water aerosol fluorescence stimulated by femtosecond laser postfilaments propagating in air - Apeksimov, Dmitrij V.; Geints, Yuri E.; Oshlakov, Viktor K.; Petrov, Aleksej V. (Applied optics)
We present the fluorescence spectra of single millimeter water droplets and micron-sized dyed water aerosol (rhodamine 6G) stimulated by a high-intensity femtosecond Ti:sapphire-laser pulse (carrier wavelength 792 nm) upon its nonlinear propagation in air. The distinctive feature of our experimental measurements is that the droplet fluorescence is obtained in the area of plasma-free pulse propagation after the pulse filamentation has already been terminated (postfilamentation region). Our results significantly expand the working area of femtosecond laser-induced fluorescence spectroscopy for remote diagnostics of atmospheric aerosols.